Efektivitas Pembelajaran Digital di Sekolah Menengah Pertama (SMP) Islam An-Nur Prima Terpadu - Asyifa Novianingtyas; Annisa Afifa Farha Abdila (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
This study discusses changes in learning methods in the digital era at SMP Islam Annur Prima Terpadu, where learning activities now rely more on screens than traditional blackboards. This change shows that learning methods have evolved along with technological developments. Digital learning is not only used to deliver learning materials, but also to make the learning process more interesting for students. This study used a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. To ensure the validity of the data, triangulation techniques were used. The data analysis process was carried out by reducing data, presenting data, and drawing conclusions. The results of the study show that digital-based learning at SMP Islam Annur Prima Terpadu has been implemented well, supported by facilities such as laptops, projectors, and online learning platforms. Teachers are also fairly prepared to use technology in the learning process. As a result, students become more interested in learning, find it easier to search for information, and become more skilled in using technology. However, there are also several challenges, such as students easily losing focus and becoming too dependent on digital devices.